Patterns and Predictors of Children’s Gender-Typed Preferences of Toys - Shojaee, Mahnaz; Cui, Ying; Shahidi, Mehrdad (European Scientific Journal, ESJ, 2016)
Focusing on social learning and cognitive developmental theories, this study pursued whether children have gender-typed preferences of toys, and also to what extent the variability of children’s preferences of toys can be determine by age, gender and social and economic status (SES). 256 children aged between 4 and 10 years old with the age mean 7.23 were selected randomly. Results revealed that children had clear gender-typed recognition and preferences for some toys. This preference was independent of biological gender factor. This study also revealed some dramatic changes in children’s responses; that is, through growing up, children gradually prefer some toys as neutral not gender-related toys. This dramatic change was different for each toy.